The evolving role of ciclosporin in the management of vernal keratoconjunctivitis - Kanda, Mumta; Manzouri, Bita (Frontiers in Ophthalmology, 2025)
In the spectrum of allergic eye disease, vernal keratoconjunctivitis (VKC) is classed as one of the most severe disease entities and can have profound effects on visual development as well as on the emotional and psychological well-being of afflicted children. The traditional mainstay of treatment for the condition, to control the ocular inflammation, has been steroids but the use of these drugs has not been without side effects. Ciclosporin offers an alternative to steroids, providing symptom relief and control of the ocular inflammation, whilst averting the problems associated with raised intraocular pressure, cataract formation and reactivation of herpes simplex keratitis, all recognised side effects of topical steroids. However, the journey to the development of a formulation of an unpreserved ciclosporin for use in human eyes has been a protracted one; the aim of this article is to outline this journey and the role of ciclosporin in the modern management of this debilitating disease.